Culture and Identity : Japanese Intellectuals during the Interwar Years. - Rimer, J. Thomas (Princeton : Princeton University Press, 2014)
This collection of essays represents the first attempt in this country to examine systematically the nature and development of modern Japanese self-consciousness as expressed through culture. The essays reveal eloquently the extent to which important aspects of Japanese intellectual life in the early twentieth century were inspired by European models of cultural criticism, ranging from Kant and Hegel to Nietzsche, Marx, Durkheim, and Bergson. Implicitly comparative, this collection raises the question whether ""late"" industrialization and related processes call forth cultural convergence).
15. Yūgen and Erhabene: Ōnishi Yoshinori's Attempt to Synthesize Japanese and Western AestheticsContributors; Index.
Print version record.
eBooks on EBSCOhost
Keywords: Japan -- Intellectual life -- 20th century; Japon -- Vie intellectuelle -- 20e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Intellectual life; Japan; 1900-1999